Local surface patterning by chitosan-stabilized gold nanoparticles using the direct mode of scanning electrochemical microscopy (SECM). - Danieli, Tamar; Mandler, Daniel. (J. Solid State Electrochem.Journal of Solid State Electrochemistry, 2013)
An approach for patterning surfaces with prepd. nanoparticles is described. Chitosan-stabilized gold nanoparticles (Au/chitosan NPs) were locally deposited on stainless steel (StSt), indium tin oxide (ITO), and highly-ordered pyrolytic graphite (HOPG). Deposition was driven by local pH gradient formed between a surface and a scanning electrochem. microscopy tip set in the direct mode. The pH at the substrate was increased upon biasing the surface by neg. potentials, which caused the redn. of water. As the pH on the surface exceeded that of pKchitosanH+\~6.3 deprotonation of the amino groups of chitosan caused the irreversible deposition of the chitosan/AuNPs. The effect of different parameters, such as tip-surface distance and time, on deposition was studied. While the potential duration showed no clear influence, smaller tip-substrate distance and more neg. potentials applied to the surface caused larger deposits. The overpotential needed for the deposition of nanoparticles on HOPG was the highest while that for StSt was the lowest. On the former, the sluggish kinetics caused the deposition of ring-shaped structures while disk-shaped deposits were formed on the other surfaces. [on SciFinder(R)]
CAPLUS AN 2013:1335253(Journal; Online Computer File)
Keywords: surface patterning chitosan stabilized gold nanoparticle scanning electrochem microscopy